IMPACT OF BRASSINOLIDE, NANO-SILICON, AND MYCORRHIZAE ON THE NUTRIENT COMPOSITION AND PRODUCTIVITY OF OLIVE TREES BASHIKA CV - Esraa AL-Jaleely; Ayad Alalaf; Suliman Kako (Mesopotamia Journal of Agriculture, 2025)
A field experiment was conducted during the 2024 growing season on 15-year-old Bashika olive trees planted in a private orchard in the village of Kasara, Duhok city, Iraqi Kurdistan, to investigate the effect of foliar spraying with three concentrations of Brassinolide (0, 2.5, and 5 mg L⁻¹) and nano-silicon fertilizer (0, 200, and 400 mg L⁻¹). The third factor involved the addition of a bio-fertilizer (mycorrhizal fungus) at three concentrations (0, 50, and 100 g tree⁻¹). The experiment used a Randomized Complete Block Design (R.C.B.D) with three factors, three replicates, and one tree per experimental unit. Therefore, the total number of trees used in the experiment was 81). The results showed that high concentrations of the three factors (5 mg L⁻¹ Brassinolide, 400 mg L⁻¹ nano-silicon, and 100 g tree⁻¹ mycorrhizae), both individually and in all binary and triple interactions, resulted in the highest significant values for traits such as nitrogen, phosphorus, and potassium concentrations, total yield, oil percentage, and anthocyanin content in the fruits. The study recommends using these concentrations for optimal results, especially for yield quantity and oil percentage in the fruits.